Cystic Tumors of the Pancreas Differential diagnosis and treatment of its variants pathological - Sánchez, Luis F; Fernández Montero, Alvaro; Silveira, Susana; Paysse, Ignacio; León, Isidro; Vallverdú, Martín (Cirugía del Uruguay, 2006)
Cysc tumors of pancreas are rare lesion, which present dificulty upon diagnosis as to their nature, whether neop/asic or inlammatoy and anatomopatho/ ogic type. lt is essential that this be determined in the preoperative stage so as to adopt a corect theapeutic conduct, although this is not always possible.